2019
DOI: 10.1002/bjs.11296
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of functional outcome and quality of life after total pancreatectomy

Abstract: BackgroundSurgeons have traditionally been reluctant to perform total pancreatectomy because of concerns for brittle diabetes and poor quality of life (QoL). Several recent studies have suggested that outcomes following total pancreatectomy have improved, but a systematic review is lacking.MethodsA systematic review was undertaken of studies reporting on outcomes after total pancreatectomy for all indications, except chronic pancreatitis. PubMed, EMBASE (Ovid), and Cochrane Library were searched (2005–2018). E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 46 publications
(241 reference statements)
0
94
0
1
Order By: Relevance
“…This will affect a patients’ life substantially and will therefore be emphasised by the surgeon and gastroenterologists, but also extensively discussed during the consult with the diabetes nurse and patient who underwent a total pancreatectomy. A recent systematic review on diabetes mellitus‐related outcomes revealed a need for further improvement of diabetes management after total pancreatectomy, especially regarding the prevention of hypoglycaemia‐related morbidity and even mortality 13 . This study also showed that quality of life seems moderately affected by total pancreatectomy.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This will affect a patients’ life substantially and will therefore be emphasised by the surgeon and gastroenterologists, but also extensively discussed during the consult with the diabetes nurse and patient who underwent a total pancreatectomy. A recent systematic review on diabetes mellitus‐related outcomes revealed a need for further improvement of diabetes management after total pancreatectomy, especially regarding the prevention of hypoglycaemia‐related morbidity and even mortality 13 . This study also showed that quality of life seems moderately affected by total pancreatectomy.…”
Section: Discussionmentioning
confidence: 57%
“…Traditionally, surgeons have been reluctant to perform total pancreatectomy because of postoperative exocrine and endocrine insufficiency, which both worsen quality of life 32 . However, taking into account the improved surgical outcome of total pancreatectomy and the improved treatment of exocrine and endocrine insufficiency, the option to remove the pancreas prophylactically has been brought up by high‐risk individuals and their family members 6 , 12–14 . The PROPAN programme offers a conceptual and informative framework for shared decision‐making in this treatment dilemma.…”
Section: Discussionmentioning
confidence: 99%
“…The survival rate was determined using the Kaplan-Meier method with survival curves compared using the log-rank test. Transitional probabilities, life expectancy, and quality adjusted life year were calculated using cohort data and reviews of peer review data over the past 20 years, [21][22][23][24][25][26][27][28][29] and decision analysis was carried out using decision-analysis software (DATA 4.0; TreeAge Software, Inc.).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the number of TPs worldwide has increased, since its subsequent endocrine and exocrine insufficiency seems to be better manageable, with an acceptable impact on quality of life. 4 Some ‘new’ pancreatic diseases (i.e. intraductal papillary mucinous neoplasms [IPMNs]) require a TP in some cases in order to achieve curation.…”
Section: Presentmentioning
confidence: 99%